-29=k-(-14)

Simple and best practice solution for -29=k-(-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -29=k-(-14) equation:


Simplifying
-29 = k + -1(-14)

Multiply -1 * -14
-29 = k + 14

Reorder the terms:
-29 = 14 + k

Solving
-29 = 14 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-29 + -1k = 14 + k + -1k

Combine like terms: k + -1k = 0
-29 + -1k = 14 + 0
-29 + -1k = 14

Add '29' to each side of the equation.
-29 + 29 + -1k = 14 + 29

Combine like terms: -29 + 29 = 0
0 + -1k = 14 + 29
-1k = 14 + 29

Combine like terms: 14 + 29 = 43
-1k = 43

Divide each side by '-1'.
k = -43

Simplifying
k = -43

See similar equations:

| 120+2x-5+3x-25+2x+2x=540 | | 1.5x^2-30x-504=0 | | y=-3x^2+4x+6 | | 3cos^2x-7cos^2x+2=0 | | 2x-3=10x-9 | | (y-3)^2/3=(10y-54)^1/3 | | 9/m | | 7(2+x)=21 | | 0.10x+0.05(4-x)=0.10(-1) | | (3x+7)=(5x-17) | | 4(2x+2)=25 | | 12y-4=-9 | | (x^2-1/5x)*(6x/x-1) | | 8x+11=12x-7 | | -5=4(2+9r)-5r | | 0.13y+0.08(y+9000)=2400 | | 4(-6p+2)=9p-1 | | -t+4=13 | | 4a+5=35 | | 5ln(x+4)-17=8 | | 12ab+6ab-9bc= | | 3x-16=4-2x | | 48s-34=48-28s | | 10-7=63 | | 51x-7=34x+163 | | .06x+x=5000 | | 3(4x)=27 | | 35-10= | | (x+5)(x+7)=105 | | sin(2x)=cos(5x) | | b^2-3=6 | | Y=9x-4xy+2x-xy |

Equations solver categories